Child Excess Weight Status, Adult Excess Weight Status, and Cardiometabolic Risk Profile - Fan, Hui; Zhu, Qi; Zhang, Xingyu (Frontiers in Pediatrics, 2020)
Background: The potential effects of excess weight status in childhood on later adult cardiometabolic risk factors have been undetermined in a Chinese population. Additionally, the potential mitigation of these effects if adult weight status returns to normalcy has been unresolved. Accordingly, we aimed to assess the association of childhood excess weight status and its long-term change with adult cardiometabolic risk factors. Methods: A cohort study from the China Health and Nutrition Survey 1991-2009 consisted of 541 participants who were measured in childhood (≥6 and <18 years) and underwent laboratory assessment in adulthood (≥18 years). In childhood, the participants were classified into 4 groups as age-sex-specific body mass index (BMI) z-score quartiles. The adult cardiometabolic risk factors included overweight and obesity, hypertension, high total cholesterol, high triglyceride, low high-density lipoprotein cholesterol, high low-density lipoprotein cholesterol, and high hemoglobin A1c. Results: The prevalence was 61.0%, 36.2%, and 19.0% for ≥1, 2, and 3 cardiometabolic risk factors, respectively, with a mean 14.9-year follow-up. There was a significant trend in the progression of the number of adult cardiometabolic risk factors across childhood BMI quartiles (P<0.001). Additionally, participants with childhood BMI z-scores≥75th percentile and adult BMI z-scores<75th percentile did not have increased cardiometabolic risks compared with those with both childhood and adulthood BMI z-scores<75th percentile. Conclusions: Our findings revealed that child excess weight status increased adult cardiometabolic risks. However, the effects of excess weight status in childhood on adult cardiometabolic risk factors were mitigated if adult weight status returned to normalcy.